Выполните умножение a^3+ba^2/a-b*a^2-b^2/a^2+2ab+b^2*(1/a+1/b). Ответ должен получиться a^2+ab/b.

Выполните умножение a^3+ba^2/a-b*a^2-b^2/a^2+2ab+b^2*(1/a+1/b). Ответ должен получиться a^2+ab/b.
Гость
Ответ(ы) на вопрос:
Гость
Выражение: a^3+b*a^2/a-b*a^2-b^2/a^2+2*a*b+b^2*(1/a+1/b) Ответ: a^3+3*b*a-b*a^2-b^2/a^2+b^2/a+b Решаем по действиям: 1. a^2/a=a a^2/a=a^(2-1) 1.1. 2-1=1 -2 _1_ 1 2. b*a+2*a*b=3*b*a 3. b^2*(1/a+1/b)=b^2/a+b b^2*(1/a+1/b)=b^2*1/a+b^2*1/b 3.1. b^2/b=b b^2/b=b^(2-1) 3.1.1. 2-1=1 -2 _1_ 1 Решаем по шагам: 1. a^3+b*a-b*a^2-b^2/a^2+2*a*b+b^2*(1/a+1/b) 1.1. a^2/a=a a^2/a=a^(2-1) 1.1.1. 2-1=1 -2 _1_ 1 2. a^3+3*b*a-b*a^2-b^2/a^2+b^2*(1/a+1/b) 2.1. b*a+2*a*b=3*b*a 3. a^3+3*b*a-b*a^2-b^2/a^2+b^2/a+b 3.1. b^2*(1/a+1/b)=b^2/a+b b^2*(1/a+1/b)=b^2*1/a+b^2*1/b 3.1.1. b^2/b=b b^2/b=b^(2-1) 3.1.1.1. 2-1=1 -2 _1_ 1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы